Malaysian Response on Challenges Facing the Global Economy of Palm Oil - Shehu, Sani (International Journal of Contemporary Sciences (IJCS), 2024)
Palm oil is a key global commodity, accounting for nearly 60% of the global vegetable oil trade. However, it faces significant criticism from Europe and the US due to issues such as deforestation, illegal resettlement, forest burning, wildlife endangerment, and human rights violations. Recently, the Covid-19 pandemic posed additional challenges, disrupting production through labor restrictions. This study explores Malaysia’s responses to these challenges, including those posed by the pandemic. Employing a qualitative exploratory design, data were gathered through document analysis and semi-structured interviews, analyzed using inductive thematic analysis with Atlas.ti 8 software. The findings highlight Malaysia's strategies, such as the Sustainable Palm Oil Manifesto, the establishment of the Council of Palm Oil Producing Countries, campaigns against anti-palm oil propaganda, and the creation of palm oil-related institutions, alongside measures to address the Covid-19 crisis. Malaysia’s responses emphasize sustainable agricultural practices aligned with the Roundtable on Sustainable Palm Oil principles while adapting to pandemic-related disruptions. These efforts demonstrate the nation’s commitment to balancing economic priorities with sustainability and resilience in the face of global challenges.